Prognostic value of cGAS-STING-IRF3 signaling in cholangiocarcinoma patients - Parawee Artbua; Naruemon Kentachalee; Sirinya Sitthirak; Prakasit Sa-Ngiamwibool; Phongsathorn Wichian; Raksawan Deenonpoe (PLoS ONE, 2026)
Cholangiocarcinoma (CCA) is an aggressive malignancy with a poor prognosis, often diagnosed at an advanced stage. Chromosomal instability (CIN), a hallmark of cancer, leads to the release of cytosolic double-stranded DNA (dsDNA), which activates the cGAS-STING pathway and its downstream immune signaling. However, the prognostic implications of this pathway in CCA remain poorly understood. This study aims to examine the cGAS-STING pathway-related proteins in CCA and their correlation with clinicopathological parameters. A total of 164 formalin-fixed paraffin-embedded (FFPE) CCA tissue samples were analyzed using tissue microarray (TMA) and immunohistochemistry (IHC). Statistical analysis assessed correlations between proteins expression and clinicopathological features were assessed using Chi-square tests, logistic regression, Kaplan–Meier survival analysis, Cox proportional hazards models, and Spearman’s rank correlation coefficient. Moderate–to–high STING expression was significantly associated with reduced tumor size and lymphovascular invasion but paradoxically correlated with short overall survival (p < 0.05). In contrast, moderate–to–high γH2AX expression predicted improved survival. IRF3 expression was significantly higher in the tubular histological subtype of CCA compared to the papillary subtype (p = 0.012), indicating a possible morphological correlation. Multivariate analysis confirmed STING as an independent prognostic marker for CCA. Our findings suggest that STING appears to function as a double-edged sword in CCA, limiting local invasion while paradoxically contributing to poor survival outcomes. IRF3 expression appears linked to histological subtypes, supporting its role in tumor biology. These markers may provide valuable insights into tumor behavior and may guide treatment strategies in CCA patients.